FAKTOR PREDISPOSING DAN ENABLING TERHADAP PEMILIHAN METODE KONTRASEPSI - Karningsih Karningsih Karningsih; Hamidah Hamidah Hamidah; Fratidhina Fratidhina Fratidhina (Jurnal Ilmu dan Teknologi Kesehatan, 2014)
The date based from Kemenkes 2011 is acceptor of family planning 76% used the metode of contraceptive short time and 24% used metode of contraceptive longtime. So the need to do research with the purpose is identify factors predisposing and enabling the metode of contraception. This research is quantitatif study with design a cross sectional using primary data. The samples this research is in the mothers the ages of fertilited in in fertile couples subdisterict health center sunday market from July to October 2013, with total samples is 120 respondens. The result univariate analyse is 60.8% used the metode of contraception short time and the metode of contraception long time 39,2%. From the result bivariate analyse is education variables with p- value = 0,046 and employment variables with p-value= 0,036 have a relationship with the metode of contraception in fertile couples. The result research is the personnel health must to give support and health education to mothers the ages of fertilited about selection the metode contraception is rational. The purpose health education is to preventive awanted pregnancy.